A Short, Efficient, and Stereoselective Synthesis of Piperine and its Analogues - Bauer, Adriano; Nam, Jun-Hyun; Maulide, Nuno (Synlett, 2019)
A quantitative synthesis of piperine from commercially available starting material is presented. The synthesis relies on a stereoselective nucleophilic attack of an in situ generated cuprate onto a cyclobutene lactone. The so-formed aryl-substituted cyclobutene spontaneously undergoes a conrotatory 4π-electrocyclic ring opening to form the 4-aryl pentadienoic acid as a single diastereoisomer. The high-yielding synthesis can be easily modulated on the aryl and on the amide moiety for the synthesis of a wide range of piperine analogues.
Keywords: total synthesis; piperine; alkaloid; cyclobutene; pericyclic reaction; stereoselective; organometallic chemistry